LEGAL ARRANGEMENTS FOR CRIMINAL ACTS OF ENVIRONMENTAL POLLUTION IN INDONESIA - Hanny Kurnia (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
Environmental law or it can also be called the law of environmental protection and management is a law that is oriented towards the environment or the environment-oriented law. The existence of this environmental law as a means that aims to restore a balanced and harmonious relationship between all subsystems in the entire ecosystem or environment, especially the human environment. The research method is included in the form of normative juridical research with secondary data used. The results of the study indicate that the legal arrangements for perpetrators of criminal acts of environmental pollution are contained in Law Number 32 of 2009 concerning Environmental Protection and Management which is regulated in Articles 96 to 120. The Law on Environmental Protection and Management introduces the threat of minimum punishment. in addition to the maximum, expansion of evidence, punishment for violations of quality standards, integration of criminal law enforcement, and regulation taking into account the ultimum remedium principle which requires the application of criminal law enforcement as a last resort after the implementation of administrative law enforcement is deemed unsuccessful. The implementation of law enforcement contained in Law Number 32 of 2009 includes the principles of environmental protection and management that are based on good governance because in every process of formulating and implementing law enforcement and prevention instruments, it is mandatory to integrate aspects of transparency, participation, accountability, and justice. The elements of a criminal act of environmental pollution include: Whoever/Every person or corporation; Intentionally or due to negligence; Doing acts that are prohibited by law; Acts that cause pollution, damage to the environment, or society; Regulated in Law Number 32 of 2009 and Regulated in other laws.